Next Generation Antenna: Large scale antenna for Mobile Communication - Inderpreet Kaur, Hari Kumar Singh, Pooja Singh, Sanjeev Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cellular Communication technology is stepping towards the 6G and particularly in the context of antennas, 6G will demand a revolution, since they are going to be designed for short wavelength (mm-waves), which easily fit in handsets. There are many practical challenges of 6G requirement, millimeter waves suffer from high attenuation due to rain, to overcome all these challenges as well as free space attenuation, high efficiency, all space coverage antenna; researching configurable, large scale array antenna and radio frequency technology, breaking through the multiband and high integrated radio frequency circuit, including low power consumption, low noise and non-linearity. The crucial challenges include the theory and implementation method of high integration RF circuit optimization design, different antenna types have been exploited for 6G networks. For device-to-device communication, we have demonstrated that is possible to reach multi-Gbps throughput using spatial multiplexing and a simple RF architecture. a new spectrum at 140 GHz that may play a major role for 6G wireless communication. Terahertz wave has high frequency and wide bandwidth which can meet the requirements of spectrum bandwidth for wireless broadband transmission also terahertz waves are having strong penetration. Terahertz wave is easily absorbed by moisture in the air, which is more suitable for high speed, short distance wireless communication. The constraints include physical barriers to sub-THz wave propagation, which can be blocked or strongly attenuated by walls, trees or even windows. Even in a clear propagation path, high-gain antennas are required Multi antenna technology, especially very large-scale antenna technology is one of the key technologies to improve the spectrum efficiency of wireless mobile communication system. The large-scale antenna system aims to offer an increased number of antenna module and alters the way in which signals are sent to device by arranging and tuning them in different ways The more antenna modules that are deployed, the higher the concentration of beams and therefore the lower the beam that each antenna needs to send information. In order to obtain large scale antenna gain, channel status information (CSI) is needed at both transmitter and receiver.